Impact of Laparoscopic Partial Nephrectomy and Open Partial Nephrectomy on Outcomes of Clear Cell Renal Cell Carcinoma - Yu, Feng; Xu, Qian; Liu, Xian-Gen (Frontiers in Surgery, 2021)
Objective: To analyze the effect of laparoscopic nephrectomy plus partial nephrectomy for the treatment of complex renal cancers. Methods: Totally 132 patients with complex renal cancers in our hospital from January 2018 to June 2020 were randomized into LPN group and OPN group, 66 cases in each group. Two weeks and three months after operation, the renal indexes, inflammatory factors, basic perioperative conditions, and incidence of complications were compared. Results: The two groups had the similar levels of Serum creatinine (SCr), Cystatin C (CysC), epidermal growth factor receptor (eGFR), C-reactive protein (CRP) and Tumor Necrosis Factor α (TNF-α)before operation(all P>0.05). Two weeks after operation, the levels of SCr and CysC were increased and were higher in the LPN group (all P<0.05). Three months after operation, SCr and CysC were decreased, but still higher than those before operation(P<0.05), and the LPN group had higher levels (P<0.05). Two weeks after operation, eGFR levels in the two groups were decreased, and lower in the LPN group (P<0.05). Three months after operation, eGFR was decreased, but still lower than before operation(P<0.05), and the LPN group expressed a lower level (P>0.05). The levels of CRP and TNF-α in the two groups increased after operation, and lower in the LPN group (P<0.05). Moreover, the LPN group had less intraoperative blood loss and shorter postoperative hospital stays, but longer blocking time compared to the OPN group (P<0.05). The LPN group showed a lower complication incidence compared with the OPN group (3.03% vs 15.15%, P<0.05). Conclusion: Laparoscopic nephrectomy plus partial nephrectomy have significant efficacy in the treatment of complex renal cancers and effectively protects renal function. Moreover, it also reduces stress and complications and shortens the length of hospital stay, and it is worthy of promotion with features of safety and feasibility.